Extremes and recurrence in dynamical systems. (2016) - Lucarini, Valerio, 1976-; Faranda, Davide; Moreira de Freitas, Ana Cristina Gomes Monteiro; Milhazes de Freitas, Jorge Miguel; Holland, Mark; Kuna, Tobias; Nicol, Matthew; Todd, Mike; Vaienti, Sandro
No abstract available